An OLG model of production with cash-in-advance constraints - Sürel, Ayşe Müjde. (Thesis (M.A.)-Bogazici University. Institute for Graduate Studies in Social Sciences, 2004., 2004)
This thesis shows the existence of the unique competitive equilibrium in a cash-in-advance economy involving overlapping generations of producers and workers. Producers have decreasing returns to scale technologies, and both producers and workers face liquidity constraints in the factor and good markets. Necessary and sufficient conditions for the existence of the monetary equilibrium are stated and the equilibrium is fully characterized. Effects of changes in the time preference of the producers, the number of producers, the number of workers and the money growth rate on the equilibrium are analyzed. The analysis reveals that money is not superneutral and that anticipated increases in the growth rate of money may lead to expansionary or contractionary impacts on the economy depending on the allocation of money transfers between young and old producers.|Keywords: Cash-in-advance, decreasing returns, limited participation, overlapping generations, superneutrality of money.
Keywords: Monetary policy -- Econometric models.; Equilibrium (Economics); Generations -- Economic aspects.